2018
DOI: 10.1002/chem.201803292
|View full text |Cite
|
Sign up to set email alerts
|

Commercially Relevant Orthogonal Multi‐Component Supramolecular Hydrogels for Programmed Cell Growth

Abstract: This study reports the ability of synthetically simple, commercially viable sugar-derived 1,3:2,4-dibenzylidenesorbitol-4',4"-diacylhydrazide (DBS-CONHNH ) to support cell growth. Simple mixing and orthogonal self-sorting can formulate heparin, agarose, and heparin-binding micelles into these gels-easily incorporating additional function. Interestingly, the components used in the gel formulation, direct the ability of cells to grow, meaning the chemical programming of these multi-component gels is directly tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 79 publications
2
22
0
Order By: Relevance
“…[20] Studies on heparin releasef rom DBS-COOH and DBS-CONHNH 2 gels individually have been reported previously by us. [9,21] We, therefore, appliedo ur already optimised method based on the use of Mallard Blue (MalB), [22] a high-affinity heparin binder,t oa nalyse heparin release from the gels by UV/Vis absorption spectroscopy.T he DBS-CONHNH 2 /DBS-COOH two-component gels loaded with heparin were prepared simplyb ya dding heparin (1 mm)t ot he LMWG mixture prior to gelation. This can be considered to be am ulti-component system.T he properties of these gels were fully studied by IR spectroscopy,m icroscopy,t hermals tability analysisa nd rheology.I na ll cases, gelation still occurred in the presence of heparin, although there was some evidencet hat the components are not all truly orthogonal (see Supporting Information for full details).…”
Section: Heparin Releasementioning
confidence: 99%
See 1 more Smart Citation
“…[20] Studies on heparin releasef rom DBS-COOH and DBS-CONHNH 2 gels individually have been reported previously by us. [9,21] We, therefore, appliedo ur already optimised method based on the use of Mallard Blue (MalB), [22] a high-affinity heparin binder,t oa nalyse heparin release from the gels by UV/Vis absorption spectroscopy.T he DBS-CONHNH 2 /DBS-COOH two-component gels loaded with heparin were prepared simplyb ya dding heparin (1 mm)t ot he LMWG mixture prior to gelation. This can be considered to be am ulti-component system.T he properties of these gels were fully studied by IR spectroscopy,m icroscopy,t hermals tability analysisa nd rheology.I na ll cases, gelation still occurred in the presence of heparin, although there was some evidencet hat the components are not all truly orthogonal (see Supporting Information for full details).…”
Section: Heparin Releasementioning
confidence: 99%
“…[8] This gel is biocompatible and supports the growth and proliferation of mousef ibroblast 3T3 cells. [9] We have previously photo-patterned polymer gels into aD BS-CONHNH 2 gel. [10] If the DBS framework is modified with carboxylic acids (DBS-COOH, Figure 1), it becomes pH responsive.…”
Section: Introductionmentioning
confidence: 99%
“…This very simple molecule forms a supramolecular hydrogel at concentrations below 0.5 wt%. This kind of hydrogels, called low molecular weight hydrogels (LMWG) or molecular hydrogels are based on the self-assembly of small gelling molecules by non-covalent interactions into a network of fibers or ribbons that entraps water [22][23][24][25][26][27][28][29][30][31][32] . Since they are only formed by small molecules and weak interactions, they give rise to soft hydrogels, suitable for the culture of some types of cells requiring very soft matrices such as neurons.…”
Section: Introductionmentioning
confidence: 99%
“…These also owing to the LMMG physical, chemical and biological characteristics, which make them very interesting vehicles as carriers of drugs, medicines, or cosmetics, and as well do to the great potential in regenerative medicine and tissue engineering . These conclusions derive primarily from the rheological similarities to the ECM, and the ability to be tuned using chemical synthesis . In this context LMMG based on peptides with high molecular weights (>1000 Da) were used owing to their ability for self‐assembling and the ability to have regenerative medicine potential in vivo in animal model systems …”
Section: Agarosementioning
confidence: 99%